A composite slurry for nitrile gloves without vulcanization accelerator and its application
By using composite slurry without vulcanization accelerator and using specific components and preparation methods, the problem of difficult cross-linked mesh structure for products such as nitrile gloves, such as rubber gloves, is solved, and its significant improvement in tensile strength, tear resistance, weather resistance and anti-aging properties is achieved.
Patent Information
- Application Number
- CN202310290943.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-03-23
AI Technical Summary
In the prior art, without using vulcanization accelerator, it is difficult to make products containing rubber materials such as nitrile gloves form a cross-linked mesh structure, resulting in poor physical properties, including shortcomings in tensile strength, tear resistance and weather resistance.
A composite slurry for nitrile gloves without vulcanization accelerator is used, which consists of nitrile latex, pH adjusting agent, zinc oxide, plasticizer, crosslinked polymer, emulsifier, inorganic filler and lubricant. Through specific component ratios and preparation methods, nitrile gloves with crosslinked network structure are formed.
It is achieved that without using vulcanization accelerator, products containing rubber materials such as nitrile gloves have good tensile strength, tear resistance, weather resistance and anti-aging properties, which are better than current vulcanization accelerator-containing products.
Smart Images

Figure BDA0004141433130000021 
Figure BDA0004141433130000032 
Figure BDA0004141433130000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of labor protection products, and particularly relates to a composite slurry for nitrile gloves without a vulcanization accelerator and application thereof. Background Art
[0002] Nitrile gloves are made of nitrile rubber and other additives. Nitrile gloves are strong and durable, have good adhesion, and have no allergic reaction to human skin. They are essential protective equipment for hand protection and preventing cross infection. They are widely used in medical care, pharmaceuticals and health, beauty salons, food processing, chemical biology and other industries.
[0003] At present, when processing products containing rubber rubber such as nitrile gloves, in order to accelerate the vulcanization speed, shorten the vulcanization time, reduce the vulcanization temperature, promote the formation of a cross-linked network structure of products containing rubber rubber such as nitrile gloves, and improve the physical and mechanical properties of products containing rubber rubber such as nitrile gloves, it is necessary to use a vulcanization accelerator. For example, patents with announcement number CN108384079B (patent name is a method for preparing wrinkled nitrile rubber gloves) and publication number CN109454791A (patent name is a method for preparing highly wear-resistant and cold-proof nitrile gloves) both use vulcanization accelerators. However, the addition of vulcanization accelerators will produce carcinogenic nitrosamines, and will also have strong oxidative corrosion to metals, causing the gloves to turn yellow and discolor, and produce irritating odors, thereby severely limiting their application in high-end fields. In order not to use vulcanization accelerators, the improvement methods currently used in the market are carried out in the direction of hydrogenating nitrile, etc., but these improvement methods cannot form a cross-linked network structure, so that the physical properties of the obtained products containing rubber rubber such as nitrile gloves are poor.
[0004] Therefore, how to make the prepared nitrile gloves and other rubber rubber products form a cross-linked network structure and have good tensile strength, tear resistance, weather resistance and other properties without using a vulcanization accelerator is a problem to be solved urgently in the present invention. Summary of the invention
[0005] The object of the present invention is to provide a composite slurry for nitrile gloves without a vulcanization accelerator and its application, so as to solve the problem raised in the above background technology that how to make the prepared nitrile gloves and other products containing rubber compounds form a cross-linked network structure and have good tensile strength, tear resistance, weather resistance and other properties without using a vulcanization accelerator.
[0006] To achieve the above-mentioned object, the present invention provides the following technical solutions: On the one hand, the present invention provides a composite slurry for nitrile gloves without vulcanization accelerator, which comprises: 40-80 (for example, 40, 45, 50, 52, 53, 54, 55, 60, 65, 70, 75, 80)% of nitrile latex, 0.5-2 (for example, 0.5, 0.53, 1, 1.5, 2)% of pH regulator, 1-3 (for example, 1, 1.2, 1.5, 2, 2.3, 2.5, 3)% of zinc oxide, 1-10 (for example, 1, 1.5, 2, 2.5, 3)% of polyols, 1-2 (for example, 1, 1.5, 2, 2.5, 3)% of polyols. 3, 3.2, 3.5, 4, 4.5, 5, 6, 7, 8, 9, 10)% of plasticizer, 0.1-5 (for example, 0.1, 0.3, 0.35, 0.5, 1, 1.3, 1.5, 2, 2.8, 3, 3.5, 4, 4.2, 4.5, 5)% of cross-linked polymer, 0.25-3 (for example, 0.25, 0.5, 0.53, 1, 1.2, 1.5, 1.8, 2, 2.8, 3)% of emulsifier, 0.1-5 (for example, 0.1, 0.3, 0.5, 1, 1.3, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5)% of inorganic filler, and the balance is deionized water.
[0007] As a further optimization, the cross-linked polymer has a structure as shown in the following formula I:
[0008]
[0009]
[0010] Wherein, n is an integer of 20-50 (including all values therebetween; for example, it can be 20, 22, 24, 25, 28, 30, 35, 38, 40, 45, 50), and * represents the connection point of the chemical bond.
[0011] As a further optimization, the mass fraction of acrylonitrile in the nitrile latex is 23-28% (for example, it can be 23%, 24%, 25%, 26%, 27%, 28%).
[0012] As a further optimization, the present invention further comprises 0.5-5 (for example, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5)% of a lubricant, wherein the lubricant is stearamide.
[0013] As a further optimization, the emulsifier is at least one of dodecylbenzene sulfonate and polyoxyethylene sorbitan fatty acid ester; and the inorganic filler is at least one of white carbon black and calcium carbonate.
[0014] As a further optimization, the pH regulator is potassium hydroxide, and the plasticizer is at least one of dioctyl terephthalate, dioctyl adipate and dioctyl phthalate.
[0015] As a further optimization, the preparation method of the cross-linked polymer comprises the following steps:
[0016] (a) adding 4-cyanostyrene and an initiator into an organic solvent 1 and mixing them uniformly to form a liquid to be added dropwise;
[0017] (b) adding an organic solvent into a reactor, heating it to 60-100° C. (e.g., 60, 70, 80, 90, 100)° C., and uniformly dropping the liquid to be added in step (a) into the reactor. After the addition is complete, post-treatment is performed to obtain an intermediate of formula I-1;
[0018]
[0019] (c) After adding a mixed solvent to the reactor, add the intermediate of formula I-1 and mix well, continue to add inorganic acid, stir until the reaction is complete, and post-treat to obtain the intermediate of formula I-2;
[0020]
[0021] (d) cooling the intermediate of formula I-2 obtained in step (c) to 0-5 (for example, 0, 2, 3, 3.5, 4, 5) ° C, adding an acyl chloride reagent dissolved in organic solvent II, stirring continuously and heating to 20-40 (for example, 20, 25, 30, 35, 40) ° C, continuing stirring until the reaction is completed, and post-treating to obtain the intermediate of formula I-3;
[0022]
[0023] (e) mixing the intermediate of formula I-3, benzoyl chloride and an organic solvent uniformly;
[0024] (f) adding sodium bicarbonate, hydrogen peroxide and deionized water into a reactor, controlling the temperature to be 10-20 (e.g., 10, 12, 15, 18, 20)° C., dripping the liquid mixed in step (e), continuing the reaction after the dripping is completed until no bubbles are generated in the system, and post-treating to obtain a cross-linked polymer.
[0025] As a further optimization, the mixed solvent includes water and an organic solvent, and the organic solvent includes at least one of tetrahydrofuran and anhydrous ethanol.
[0026] Among them, when using the components and mass of the composite slurry for nitrile gloves without vulcanization accelerator of the present invention to prepare the composite slurry for nitrile gloves without vulcanization accelerator, the following steps are included:
[0027] Take the components of the required mass of the formula and mix them evenly. The stirring speed during mixing is 100-200 (for example, 100, 120, 150, 180, 200) r / min, and the stirring time is 15-20 (for example, 15, 16, 17, 18, 20) h to obtain a composite slurry for nitrile gloves without a vulcanization accelerator.
[0028] On the other hand, the present invention also provides a use of a composite slurry for nitrile gloves that does not contain a vulcanization accelerator in the preparation of nitrile gloves.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) Products containing rubber compounds such as nitrile gloves prepared using the composite slurry for nitrile gloves without vulcanization accelerator of the present invention have good tensile strength, tear resistance, weather resistance, and excellent anti-aging performance;
[0031] (2) The cross-linked polymer involved in the present invention is a macromolecular photoinitiator. The composite slurry for nitrile gloves containing the cross-linked polymer can undergo 20 or even 50 cross-linking reactions. The mechanical properties of the prepared nitrile gloves and other products containing rubber compounds are better than those of the currently available products containing vulcanization accelerators. DETAILED DESCRIPTION
[0032] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0033] In the following examples, except for the compound of formula Ⅰ-A and the compound of formula Ⅰ-B, the other compound monomers and related reagents used can be purchased from the market.
[0034] The preparation method of the compound of formula Ⅰ-A comprises the following steps:
[0035] (a) adding 20 mol of 4-cyanostyrene and 1.1 mol of azobisisobutyronitrile to 1000 mL of ethyl acetate and mixing them uniformly to form a solution to be added dropwise;
[0036] (b) 1000 mL of ethyl acetate was added to the reactor, the temperature was raised to 80° C., the solution to be added in step (a) was uniformly added dropwise to the reactor for 4 hours. After the reaction was completed, the ethyl acetate in the system was removed by vacuum concentration to obtain Formula I-1-A intermediates;
[0037] (c) After adding 100 mL of tetrahydrofuran, 100 mL of water and 50 mL of anhydrous ethanol to the reactor and mixing evenly, 0.1 mol of the intermediate of formula I-1-A was added and mixed evenly, and 250 mL of concentrated hydrochloric acid with a mass percentage concentration of 34% was added, and stirred for 24 hours. The tetrahydrofuran, water and ethanol in the system were removed by vacuum concentration, and extracted with 100 mL of dichloromethane to obtain formula I-2-A. intermediates;
[0038] (d) The intermediate of formula I-2-A obtained in step (c) was cooled to 2°C, 160 mL of dichlorothionyl and 20 mL of N,N-dimethylformamide were added, and the mixture was stirred for 15 h, then heated to 30°C, stirred for 8 h, and concentrated under reduced pressure to remove excess dichlorothionyl and N,N-dimethylformamide in the system to obtain formula I-3-A intermediates;
[0039] (e) 0.1 mol of the intermediate of formula Ⅰ-3-A, 2 mol of benzoyl chloride, and 50 mL of tetrahydrofuran were mixed uniformly;
[0040] (f) 1 mol of sodium bicarbonate, 2.5 mol of hydrogen peroxide, and 100 mL of deionized water were added to the reactor, the temperature was controlled to be 12° C., the mixed liquid in step (e) was added dropwise, and the reaction was continued until no bubbles were generated in the system. The organic phase was collected, concentrated under reduced pressure to remove tetrahydrofuran in the system, and 200 mL of anhydrous ethanol was added to pulp, and filtered to obtain Formula I-A. of compounds.
[0041] The preparation method of the compound of formula I-B comprises the following steps:
[0042] (a) adding 30 mol of 4-cyanostyrene and 1.5 mol of azobisisobutyronitrile to 1500 mL of ethyl acetate and mixing them uniformly to form a solution to be added dropwise;
[0043] (b) 1000 mL of ethyl acetate was added to the reactor, the temperature was raised to 70° C., the solution to be added in step (a) was uniformly added to the reactor, the addition time was 5 h, and the ethyl acetate in the system was removed by vacuum concentration to obtain Formula I-1-B intermediates;
[0044] (c) After adding 140 mL of tetrahydrofuran, 130 mL of water and 60 mL of anhydrous ethanol to the reactor and mixing evenly, 0.1 mol of the intermediate of formula I-1-B was added and mixed evenly, and 350 mL of concentrated hydrochloric acid with a mass percentage concentration of 36% was added, stirred for 28 hours, and concentrated under reduced pressure to remove tetrahydrofuran, water and ethanol in the system, and extracted with 150 mL of dichloromethane to obtain formula I-2-B intermediates;
[0045] (d) The intermediate of formula I-2-B obtained in step (c) was cooled to 3°C, 230 mL of dichlorothionyl and 40 mL of N,N-dimethylformamide were added, and the mixture was stirred for 16 h, then heated to 30°C, stirred for 7 h, and concentrated under reduced pressure to remove excess dichlorothionyl and N,N-dimethylformamide in the system to obtain formula I-3-B intermediates;
[0046] (e) 0.1 mol of the intermediate of formula Ⅰ-3-B, 3 mol of benzoyl chloride, and 70 mL of tetrahydrofuran were mixed uniformly;
[0047] (f) 1.5 mol of sodium bicarbonate, 4 mol of hydrogen peroxide, and 150 mL of deionized water were added to the reactor, the temperature was controlled to be 15° C., the liquid mixed in step (e) was added dropwise, and the reaction was continued until no bubbles were generated in the system. The organic phase was collected, concentrated under reduced pressure to remove tetrahydrofuran in the system, and 150 mL of anhydrous ethanol was added to pulp, and filtered to obtain Formula I-B of compounds.
[0048] Embodiment 1:
[0049] The composite slurry for nitrile gloves without vulcanization accelerator comprises, based on the total mass content of the composite slurry for nitrile gloves being 100%, 54% of nitrile latex, 0.53% of potassium hydroxide, 2% of zinc oxide, 3.2% of dioctyl terephthalate, 0.5% of the compound of formula Ⅰ-A, 0.53% of dodecylbenzene sulfonate, 0.3% of white carbon black, 1.5% of stearamide, and the balance is deionized water, wherein the mass fraction of acrylonitrile in the nitrile latex is 25%.
[0050] Embodiment 2:
[0051] The composite slurry for nitrile gloves without vulcanization accelerator comprises, based on the total mass content of the composite slurry for nitrile gloves being 100%, 53% of nitrile latex, 0.5% of potassium hydroxide, 2.3% of zinc oxide, 3% of dioctyl adipate, 0.35% of the compound of formula I-B, 1% of polyoxyethylene sorbitan fatty acid ester, 0.5% of calcium carbonate, 1% of stearamide, and the balance is deionized water, wherein the mass fraction of acrylonitrile in the nitrile latex is 26%.
[0052] Embodiment 3:
[0053] The composite slurry for nitrile gloves without vulcanization accelerator comprises, based on the total mass content of the composite slurry for nitrile gloves being 100%, 53% of nitrile latex, 0.5% of potassium hydroxide, 2.3% of zinc oxide, 2% of dioctyl adipate, 1.5% of dioctyl phthalate, 0.3% of the compound of formula I-A, 1% of the compound of formula I-B, 1% of dodecylbenzene sulfonate, 0.5% of white carbon black, 0.5% of stearamide, and the balance is deionized water, wherein the mass fraction of acrylonitrile in the nitrile latex is 28%.
[0054] Example 4: A composite slurry for nitrile gloves without a vulcanization accelerator, the components used and the masses of each component are basically the same as those in Example 1, except that the mass fraction of acrylonitrile in the nitrile latex is replaced by 29% of the mass fraction of acrylonitrile in the nitrile latex.
[0055] Embodiment 5:
[0056] The composite slurry for nitrile gloves without vulcanization accelerator uses the same components and the masses of each component as in Example 1, except that the mass fraction of acrylonitrile in the nitrile latex is replaced by 22% of the mass fraction of acrylonitrile in the nitrile latex instead of 25%.
[0057] Comparative Example 1:
[0058] The composite slurry for nitrile gloves without vulcanization accelerator has the same components and the same mass as those in Example 1, except that the compound of formula Ⅰ-A is not added.
[0059] Comparative Example 2:
[0060] The composite slurry for nitrile gloves without vulcanization accelerator uses the same components and the same mass as those in Example 1, except that the compound of formula Ⅰ-A is replaced by sodium di-n-butyl dithiocarbamate, wherein sodium di-n-butyl dithiocarbamate is a vulcanization accelerator provided by Shijiazhuang Shengpeng Chemical Co., Ltd.
[0061] When preparing the composite slurry for nitrile gloves without vulcanization accelerator required by Examples 1 to 5 and Comparative Examples 1 to 2, the following production process is adopted:
[0062] Take the required mass of nitrile latex, pH regulator, zinc oxide, plasticizer, cross-linked polymer, deionized water, emulsifier, inorganic filler and lubricant, and mix them evenly. The stirring speed is 150r / min and the stirring time is 15h.
[0063] When preparing the samples to be tested, the composite slurries for nitrile gloves without vulcanization accelerator prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were poured into molds respectively and subjected to uniform gluing, low-temperature drying (drying temperature of 50° C., drying time of 50 min), high-temperature drying (drying temperature of 130° C., drying time of 30 min), and demolding to obtain the samples required for the experiment.
[0064] The test method is as follows:
[0065] Tensile strength test: Tested in accordance with ASTM D412 standard.
[0066] 70℃ aging for 168h elongation at break test: according to EN455 standard.
[0067] Tear resistance test: according to EN388 standard.
[0068] The test results are shown in Table 1, as follows:
[0069] Table 1
[0070]
[0071] From the comparison between Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the product prepared by the composite slurry for nitrile gloves containing a cross-linked polymer and no vulcanization accelerator in the present invention has significantly improved properties such as tensile strength, tear resistance and weather resistance;
[0072] By comparing Example 1, Example 4 and Example 5, it can be seen that when the mass fraction of acrylonitrile in the nitrile latex is 23-28%, the product prepared by the composite slurry for nitrile gloves containing a cross-linked polymer and no vulcanization accelerator in the present invention has better tensile strength, tear resistance and weather resistance.
[0073] From the comparison of Examples 1 to 5, it can be seen that the products made from the composite slurry for nitrile gloves without vulcanization accelerator of different components and qualities have a tensile strength of more than 32.5 MPa, a tear resistance of more than level 3, and an elongation at break after aging at 70°C for 168 hours of more than 606%, and can even reach 681%.
[0074] In summary, products containing rubber compounds such as nitrile gloves made using the composite slurry for nitrile gloves without vulcanization accelerator prepared by the present invention have good tensile strength, tear resistance, weather resistance, and excellent anti-aging performance.
[0075] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite slurry for nitrile gloves without vulcanization accelerator, characterized in that: Based on the total mass content of the composite slurry for nitrile gloves being 100%, it comprises: 40-80% of nitrile latex, 0.5-2% of pH regulator, 1-3% of zinc oxide, 1-10% of plasticizer, 0.1-5% of cross-linked polymer, 0.25-3% of emulsifier, 0.1-5% of inorganic filler, and the balance is deionized water; The cross-linked polymer has a structure as shown in the following formula I: Wherein, n is an integer of 20-50, and * represents the connection point of the chemical bond; The preparation method of the cross-linked polymer comprises the following steps: (a) adding 4-cyanostyrene and an initiator into an organic solvent 1 and mixing them uniformly to form a liquid to be added dropwise; (b) adding an organic solvent into a reactor, raising the temperature to 60-100° C., and uniformly dropping the liquid to be added in step (a) into the reactor. After the dropwise addition is completed, post-treatment is performed to obtain an intermediate of formula Ⅰ-1; (c) After adding a mixed solvent to the reactor, add the intermediate of formula I-1 and mix well, continue to add inorganic acid, stir until the reaction is complete, and post-treat to obtain the intermediate of formula I-2; (d) cooling the intermediate of formula I-2 obtained in step (c) to 0-5°C, adding an acyl chloride reagent dissolved in organic solvent II, stirring continuously and heating to 20-40°C, stirring continuously until the reaction is complete, and post-treating to obtain an intermediate of formula I-3; (e) mixing the intermediate of formula I-3, benzoyl chloride and an organic solvent uniformly; (f) adding sodium bicarbonate, hydrogen peroxide and deionized water into a reactor, controlling the temperature at 10-20° C., and dripping the liquid mixed in step (e). After the dripping is completed, the reaction is continued until no bubbles are generated in the system, and post-processing is performed to obtain a cross-linked polymer.
2. The composite slurry for nitrile gloves without vulcanization accelerator according to claim 1, characterized in that: The mass fraction of acrylonitrile in the nitrile latex is 23-28%.
3. The composite slurry for nitrile gloves without vulcanization accelerator according to claim 1, characterized in that: The invention also contains 0.5-5% of a lubricant, which is stearamide.
4. The composite slurry for nitrile gloves without vulcanization accelerator according to claim 1, characterized in that: The emulsifier is at least one of dodecylbenzene sulfonate and polyoxyethylene sorbitan fatty acid ester.
5. The composite slurry for nitrile gloves without vulcanization accelerator according to claim 1, characterized in that: The inorganic filler is at least one of white carbon black and calcium carbonate.
6. The composite slurry for nitrile gloves without vulcanization accelerator according to claim 1, characterized in that: The pH regulator is potassium hydroxide, and the plasticizer is at least one of dioctyl terephthalate, dioctyl adipate, and dioctyl phthalate.
7. Use of the composite slurry for nitrile gloves without vulcanization accelerator according to any one of claims 1 to 6 in the preparation of nitrile gloves.
Citation Information
Patent Citations
A method for preparing nitrile rubber wrinkled gloves
CN108384079B
High-abrasion-resistance cold-proof butyronitrile glove preparation method
CN109454791A
Glove dipping composition, method for manufacturing gloves, and gloves
CN109561742A
Elastomeric gloves and methods for their production
CN111629621A